(untitled) (American Journal of Islam and Society, 2014)
The hadith compilations are filled with the Prophet’s prophecies and predictions about the future, be it the future state of Muslims, the outcomes of battles, the signs of the end times, and so on. If Muslims are uncertain as to how and when some of these may come to pass, there is little doubt that, somehow, someway, they will certainly do so. Muslims’ confidence in the latter scenario stems from their unflinching belief in Muhammad as God’s messenger. The Sunan Abī Dāwūd, one of six authentic Sunni hadith collections, contains a hadith in which the Prophet predicts that one day Muslims, as a group, will be so weak and insignificant that other nations (umam) will compete to snatch them, just like feeding animals (akalah) challenge one another over thir feed (qaṣ‘ah; lit.: large bowl). He insists that this will not be due to the Muslims’ smaller numbers, because their numbers will be huge; rather, they will be as worthless as “the scum of a torrent” (ghuthā’ al-sayl), which is unworthy of being kept for any future use and thus deserves to be removed and discarded. At this time, the hadith continues, non-Muslims will have not one iota of fear and apprehension (mahāba) of Muslims, but the latter will have already resigned themselves to their own feebleness (wahn) and thus be gripped with fear of non-Muslims ...